Regional integration of the East Asian stock markets: An empirical assessment - Boubakri, Salem (2015)
The aim of this paper is to study the dynamics of regional financial integration in East Asia over the 1990:01-2012:08 period. To this end, we use the international capital asset pricing model (ICAPM) to assess the evolution of financial market integration through time and evaluate their risk premia. We also construct an Asian currency basket in order to obtain a reference currency in this area. Our empirical analysis is based on the multivariate GARCH-DCC approach with time-varying correlations. Our results show that the East Asian stock markets were partially segmented (except for Japan) within their region until approximately 2008. However, the last years are characterized by an upward trend in the regional integration of stock markets. Our findings also show that the risk premium related to regional stock markets is significant for all countries. © 2015 Elsevier Ltd.